Introduction to Sharia Economics and Financial Literacy for Elementary School Students - Rihfenti Ernayani; Citra Dewi; Nur Dafiq; Rosdarni Rosdarni (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This research delves into the introduction of Sharia Economics and financial literacy among students at the International School of Kuala Lumpur. Recognizing the importance of financial education and ethical financial practices, especially in diverse educational settings, this study aims to bridge the gap in understanding Islamic finance principles and fostering financial literacy among students. The background of the problem lies in the necessity to equip students with comprehensive knowledge of Sharia Economics, aligning with the multicultural context of Kuala Lumpur. The primary objective of this research is to assess the effectiveness of integrating Sharia Economics education and financial literacy within the curriculum of an international school. Through a systematic methodology, including surveys, workshops, and curriculum analysis, the research evaluates the students' understanding and engagement with Sharia Economics principles and financial literacy concepts. The findings reveal the significance of incorporating Sharia Economics and financial literacy education in the curriculum, highlighting improved awareness and comprehension among students. The integration of real-life examples and interactive learning methods enhances students' practical understanding of ethical financial practices within the Islamic framework. In conclusion, this research underscores the importance of promoting Sharia Economics education and financial literacy among students in international schools, emphasizing its role in shaping responsible financial behaviors and fostering a deeper understanding of ethical economic principles. The implications of this study extend beyond the classroom, emphasizing the broader significance of financial education in promoting economic sustainability and ethical financial practices in diverse global contexts.